Effect of simultaneous presence of anti-blood group A/B and -HLA antibodies on clinical outcomes in kidney transplantation across positive crossmatch: a nationwide cohort study - Kwon, Hyunwook (Sci Rep, 2019)
ABO-incompatible (ABOi) and positive crossmatch (XM) kidney transplantation (KT) have been considered immunologically challenging. The present study analyzed the clinical outcomes in XM positive KT based on ABO incompatibility. We used data from the Korea Organ Transplantation Registry, a nationwide database, and a single-center registry. A total of 263 patients with positive XM were divided into an ABO compatible (ABOc) & XM positive (ABOc/XM+, n = 176) group and an ABOi & XM positive (ABOi/XM+, n = 87) group. The overall rejection rate one year after KT was significantly higher in the ABOi/XM+ group than in the ABOc/XM+ group (P < 0.01). A total of four mortalities occurred, all in the ABOi/XM+ patients (P < 0.01). There were no differences in surgical complications or the occurrence of infection-related complications, including BK virus nephropathy. Multivariate analysis indicated that female vs. male (odds ratio (OR), 2.27; P = 0.03), DSA class I (MFI/1000) (OR, 1.10; P = 0.03), DSA class II (MFI/1000) (OR, 1.10; P < 0.01), and ABOi & XM+ status (OR, 2.38; P < 0.01) were significant risk factors for acute rejection during the year after transplantation. Overall graft survival was inferior in ABOi/XM+ patients than in ABOc/XM+ patients (P = 0.02). ABO incompatibility in XM-positive KT patients was found to be a significant risk factor for the development of rejection within one year after transplantation as well as for long-term graft survival. The anti-blood group A, B and anti-HLA antibodies may show synergistic activity.